Understanding user characteristics as antecedents of technostress towards HRMIS : a mixed-method study - Hadziroh Ibrahim,; Faridahwati Mohd Shamsudin,; Md Lazim Mohd Zin,; Chandrakantan Subramaniam, (Penerbit Universiti Kebangsaan Malaysia, 2018)
This study aims to explore the effects of user characteristics as antecedents of technostress towards human resource management information system (HRMIS) in government agencies of Malaysia. To address the research objective, we conducted an exploratory mixed-method study which involved both the semi-structured interviews with HRMIS experts from three state governments of Malaysia and the survey questionnaire of HRMIS end-users. Findings from the content analysis of the interview data have identified three key characteristics of users, namely, attitude, technology readiness, and readiness for change, and have suggested that these characteristics are relevant antecedents of technostress. The PLS analysis from the quantitative survey results have revealed that the experiences of technostress towards HRMIS can be influenced only by user’s attitude. From the theoretical aspects and practical implications, this study provides the researchers insights and understanding of the phenomena for future exploratory studies and valuable guidance for the practitioners to manage strains associated with technostress both in the public and the private sectors. More importantly, this study has not only provided new empirical evidence that extends the generalizability of previous findings particularly on technostress and job outcomes but also different from previous studies in the field of information system by examining the antecedents of technostress in the context of human resource information system (HRIS).